2015
DOI: 10.1063/1.4905875
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional spatial manipulation of microparticles in continuous flows in acoustofluidic systems

Abstract: We report a modeling and experimental study of techniques to acoustically focus particles flowing through a microfluidic channel. Our theoretical model differs from prior works in that we solve an approximate 2-D wave transmission model that accounts for wave propagation in both the solid and fluid phases. Our simulations indicate that particles can be effectively focused at driving frequencies as high as 10% off of the resonant condition. This conclusion is supported by experiments on the acoustic focusing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…We found that these particles, which have a positive acoustic contrast factor, focused along the pressure node as expected. 6 We also injected red fluorescent particles with a negative acoustic contrast factor (i.e., ɸ ≈ −0.88, synthesized from a process described previously) 8 to verify that our device could induce their concentration along the pressure antinodes ( Figure 2C). …”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that these particles, which have a positive acoustic contrast factor, focused along the pressure node as expected. 6 We also injected red fluorescent particles with a negative acoustic contrast factor (i.e., ɸ ≈ −0.88, synthesized from a process described previously) 8 to verify that our device could induce their concentration along the pressure antinodes ( Figure 2C). …”
Section: Representative Resultsmentioning
confidence: 99%
“…Turn on the function generator and power amplifier to begin actuating the PZT transducer. 6 1. To estimate the resonant frequency of the device, follow the equation c = λ * ƒ, where c is the speed of sound of the medium (i.e., water), λ is the acoustic wavelength and ƒ is the frequency of the PZT transducer.…”
Section: Operating the Acoustofluidic Devicementioning
confidence: 99%
“…The third class of active cell sorters uses acoustic forces to sort cells via: (i) bulk acoustic standing waves (), (ii) standing surface acoustic waves (SSAWs) () or (iii) bulk acoustic travelling waves . Petersson et al first demonstrated the utility of bulk acoustic standing waves by separating lipids from blood cells .…”
Section: Leading Microfluidic Sorting Devicesmentioning
confidence: 99%
“…Leveraging existing frameworks, such as the monolithic techniques from the semiconductor industry, as well as emerging techniques (e.g., 3D printing) may help to overcome these challenges (99)(100)(101); however, the ideal material for industrial-scale productions of microfluidic devices ultimately depends on the separation technique at hand. For example, microfluidic devices supporting bulk acoustic standing waves must be made from rigid materials, such as silicon, glass, or polymethyl methacrylate (PMMA) (76,102), whereas optoelectronic devices are typically made, at least in part, from transparent, electrically conductive materials, such as indium tin oxide (ITO) (88).…”
Section: Device-related Barriersmentioning
confidence: 99%
“…For SAW-based devices, diverse manipulation functions, such as trapping [26,27], patterning [28,29], separation [30,31], concentration [32,33], mixing [34,35], and rotation [36,37] have been implemented by various groups. For BAW-based devices, manipulation functions such as levitation [38,39], assembly [40,41], focusing [42,43] and sorting [44] have also been realized by many researchers.…”
Section: Introductionmentioning
confidence: 99%